A sulfur host based on titanium monoxide@carbon hollow spheres for advanced lithium–sulfur batteries - Zhen Li (Nature Portfolio, 2016)
The promise of lithium-sulfur batteries with higher energy densities than lithium-ion is hindered by the insulating nature of sulfur and dissolution of polysulfides. Here the authors design titanium monoxide/carbon hollow nanospheres that overcome both obstacles, enabling improved electrochemical properties.